1992
DOI: 10.1136/adc.67.8.1030
|View full text |Cite
|
Sign up to set email alerts
|

Reversible cerebral shrinkage in kwashiorkor: an MRI study.

Abstract: Protein energy malnutrition is associated with cerebral atrophy which may be detrimental to intellectual development. The aim ofthis study was to document the anatomical abnormalities which lead to the appearance of cerebral atrophy using magnetic resonance imaging (MRI) in the acute stage of kwashiorkor and to monitor changes during nutritional rehabilitation.Twelve children aged 6 to 37 months requiring admission to hospital for the treatment of kwashiorkor were studied. The children were evaluated clinicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 5 publications
2
32
0
1
Order By: Relevance
“…In our follow up, we found significant elevation of serum iron,ferritin,albumin and NKA in children after recovery from malnutrition. Also, follow up MRI revealed improvement of previous atrophic changes in 90% of cases and this comes in concordance with Elsherif et al study 2012 [20] Gunston et al, suggested that loss of myelin lipid accounts for the cerebral shrinkage seen in their patients and restoration of lipid to the myelin membrane with re-feeding accounts for the reversal of cerebral shrinkage [41] . Additionally, we found significant improvement of latencies detected by VEPs after nutritional rehabilitation.…”
Section: Discussionsupporting
confidence: 75%
“…In our follow up, we found significant elevation of serum iron,ferritin,albumin and NKA in children after recovery from malnutrition. Also, follow up MRI revealed improvement of previous atrophic changes in 90% of cases and this comes in concordance with Elsherif et al study 2012 [20] Gunston et al, suggested that loss of myelin lipid accounts for the cerebral shrinkage seen in their patients and restoration of lipid to the myelin membrane with re-feeding accounts for the reversal of cerebral shrinkage [41] . Additionally, we found significant improvement of latencies detected by VEPs after nutritional rehabilitation.…”
Section: Discussionsupporting
confidence: 75%
“…Additionally, in that same plane and in 2D, the analysis for the cerebellum, the approximate number of pixels was 2017.33 ± 28.87 and 1994.67 ± 58.24 for the control group and the experimental group, respectively; this is a difference of approximately 3 %. These results corroborate the model that a malnourished brain has greater "water" areas (in our case for the third ventricle) and displays signs of abnormal brain development (especially in the cerebellum) [34]. Therefore, a three-dimensional rendering process was computed to observe anatomical differences between representative subjects of the groups.…”
Section: Bold Responsesupporting
confidence: 58%
“…Others have found that IGF-1 levels are reduced in patients with anorexia nervosa (Counts, Gwirtsman, Carlsson, Lesem, & Cutler, 1992;Golden et al, 1994;Grinspoon, Baum, et al, 1996;Grinspoon, Gulick, et al, 1996;Hall, Lundin, & Pó voa, 1988;Hill, Hill, McClain, Humphries, & McClain, 1993;Hochberg et al, 1992;Rappaport, Prevot, & Czernichow, 1980;Tanaka, Maesaka, & Suwa, 1985;Winterer et al, 1985). As in anorexic patients, CT and MRI studies of patients with protein caloric malnutrition have demonstrated reduced brain tissue volumes, which are reversible following nutritional normalization (Gunston, Burkimsher, Malan, & Sive, 1992;Househam, 1991;Househam & De Villiers, 1987). Note: CSF = cerebrospinal fluid.…”
Section: Discussionmentioning
confidence: 91%
“…There is more direct evidence that the reduction of growth hormone receptor levels that accompanies fasting and starvation causes these low levels of IGF-1 because growth hormone stimulation of its receptors is necessary for the liver to produce IGF-1 (Gunston et al, 1992).…”
Section: Discussionmentioning
confidence: 99%